STUDI EFISIENSI BANK UMUM DI INDONESIA TAHUN 2002 - 2013 : Komparasi Faktor-Faktor Penjelas Efisiensi Antara Bank Umum Konvensional Dengan Bank Umum Syariah - Jaelani, - (2015)
This study is aimed to analyze the efficiency of commercial banks in Indonesia and the factors that explain in efficiency levels, which is based on the intermediary and the agency theory, this is in line with the phenomenon of the low efficiency of banks in Indonesia, which is shown by the value of BOPO and NIM are still high and likely to rise, it is a serious gap. This research uses a quantitative approach, with three stages. Firstly, it measures technical efficiency of commercial banks using Data Envelopment Analysis /DEA (Casu and Molyneux, 2000). Secondly, it uses Tobit regression models (Stavárek, 2003) to examine the factors that explain in efficiency levels of commercial banks. And lastly, it analyzes the of Conventional Bank (BUK) and the Islamic Banks (BUS) separately. Input-output variables are selected with the intermediation approach. The input variables include DPK, Cost of Fixed Assets, and Labor Costs, while the output variables include Productive Assets, Interest Income, and Feebased Income. Meanwhile variable as CAR, LDR / FDR, NPL / NPF, NIM / NOM, ROA, ROE, inflation, GDP, and GWM are used as the factors that explain in efficiency levels. The results of this study show that for the year 2002-2013, the low level of efficiency of commercial banks. This findings is interesting, it proves that the commercial banks have not run their intermediation optimally. The level of efficiency in the BUS is lower than that is in the BUK. It indicates that the BUS group has not applied the practicesin Islamic principles optimally. The empirical on testing the factors that explain in efficiency levels, for the variable LDR / FDR, NPL / NPF, NIM / NOM, ROA, ROE, inflation and GDP significantly affect the level of efficiency of commercial banks, while the variable CAR and GWM insignificantly have influence weak. So that a comparative study, showed that there was a difference between groups BUK with BUS, because the two groups have different principles relating to interest. Keywords: Efficiency of Banks, Input-Output, the Explanatory Factors of Banks Efficiency Studi ini bertujuan untuk menganalisis efisiensi Bank umum di Indonesia dan faktor-faktor penjelas yang mempengaruhinya, berdasarkan teori intermediasi (intermediary theory) dan teori keagenan, hal ini sejalan dengan fenomena rendahnya efisiensi bank di Indonesia yang ditunjukan oleh nilai BOPO dan NIM yang masih tinggi dan dan cenderung naik, merupakan gap yang serius. Penelitian ini menggunakan pendekatan kuantitatif, dengan dilakukan tiga tahap. Pertama, mengukur efisiensi Bank menggunakan metode Data Envelopment Analysis/DEA (Casu and Molyneux, 2000), Kedua, menggunakan regresi model Tobit (Stavárek, 2003), dan ketiga, melakukan analisis komporasi faktor-faktor penjelas tingkat efisiensi antara Bank Umum Konvensional (BUK) dengan Bank Umum Syariah (BUS) secara terpisah. Variabel input-output dipilih dengan pendekatan intermediasi. Variabel input: DPK, Biaya Aktiva Tetap, dan Biaya Tenaga Kerja. Sementara variabel output: Aktiva Produktif, Pendapatan Bunga, dan feebased income. Selanjutnya variabel CAR, LDR/FDR, NPL/NPF, NIM/NOM, ROA, ROE, dan Inflasi, PDB, dan GWM; sebagai faktor-faktor penjelas tingkat efisiensi. Hasil penelitian menunjukan tahun 2002-2013, tingkat efisiensi bank umum rendah, Temuan ini menarik, artinya bank umum belum menjalankan intermediasi secara optimal. Tingkat efisiensi BUS lebih rendah dibandingkan BUK, diindikasikan BUS belum optimal mengaplikasikan praktek prinsip syariah. Temuan empiris pengujian faktor-faktor penjelas, untuk variabel LDR/FDR, NPL/NPF, NIM/NOM, ROA, ROE, Inflasi dan PDB berpengaruh secara signifikan terhadap tingkat efisiensi bank umum, sedangkan variabel CAR dan GWM memiliki pengaruh yang lemah. Selanjutnya studi komparasi, menunjukkan ada perbedaan antara BUK dengan BUS, karena keduanya memiliki prinsip yang berbeda terkait dengan bunga. Kata kunci: Efisiensi Bank, Input-Outpt, Faktor-faktor Penjelas Efisiensi Bank.